RAB-A2a dependent membrane traffic in Arabidopsis thaliana - Woollard, A (2013)
Rab GTPases are major regulatory proteins of vesicle traffic and thus responsible for membrane identity, vesicle targeting and vesicle fusion. The angiosperm Rab GTPase family is grouped into eight clades (Rab-A to Rab-H) that are broadly conserved in animals and yeasts. It has been proposed that the Rab-A clade has diversified in land plants giving rise to six plant- specific structural subclasses, Rab-A1 to Rab-A6. Previous work suggests that the Arabidopsis Rab-A2 and Rab-A3 proteins define a novel endosomal compartment that lies on a pathway between the Golgi and the plasma membrane. In dividing cells, the Rab-A2/A3 compartment is implicated in biosynthetic traffic to the cell plate but it is unclear what traffics through this compartment in non-dividing cells. In this project, I investigated a range of membrane trafficking pathways in Arabidopsis thaliana. These were probed for dependency on RAB-A2a function, using the dominant negative approach combined with fluorescent marker technology. The data presented in this thesis suggests that RAB-A2a acts on a protein recycling pathway that is used by PIN2:GFP.